Baby dumping: definitions and related terms in the legal perspectives - Termizi, Mazbah; Imam Supaat, Dina (2019)
The terms baby dumping are not being defined in the legal perspective. The definition is needed in order to ensure the punishment and enforcement of laws related to the act can be done accordingly. The term also is associated with other act, i.e. child abandonment, filicide, infanticide, neonaticide, etc. This paper aim to find the correct definition of baby dumping and how it is related in the legal perspective.